Single-cell analysis highlights a population of Th17-polarized CD4+ naïve T cells showing IL6/JAK3/STAT3 activation in pediatric severe aplastic anemia. Issue 136 (April 2023) - Zhang, Jingliao; Liu, Tianfeng; Duan, Yongjuan; Chang, Yanxia; Chang, Lixian; Liu, Chao; Chen, Xiaoyan; Cheng, Xuelian; Li, Tianyu; Yang, Wenyu; Chen, Xiaojuan; Guo, Ye; et al.
Abstract: Acquired aplastic anemia (AA) is recognized as an immune-mediated disorder resulting from active destruction of hematopoietic cells in bone marrow (BM) by effector T lymphocytes. Bulk genomic landscape analysis and transcriptomic profiling have contributed to a better understanding of the recurrent cytogenetic abnormalities and immunologic cues associated with the onset of hematopoietic destruction. However, the functional mechanistic determinants underlying the complexity of heterogeneous T lymphocyte populations as well as their correlation with clinical outcomes remain to be elucidated. To uncover dysfunctional mechanisms acting within the heterogeneous marrow-infiltrating immune environment and examine their pathogenic interplay with the hematopoietic stem/progenitor pool, we exploited single-cell mass cytometry for BM mononuclear cells of severe AA (SAA) patients pre- and post-immunosuppressive therapy, in contrast to those of healthy donors. Alignment of BM cellular composition with hematopoietic developmental trajectories revealed potential functional roles for non-canonically activated CD4 + naïve T cells in newly-diagnosed pediatric cases of SAA. Furthermore, single-cell transcriptomic profiling highlighted a population of Th17-polarized CD4 + CAMK4 + naïve T cells showing activation of the IL-6/JAK3/STAT3 pathway, while gene signature dissection indicated a predisposition to proinflammatory pathogenesis. Retrospective validation from our SAA cohort of 231 patients revealed high plasma levels of IL-6 as an independent risk factor of delayed hematopoietic response to antithymocyte globulin-based immunosuppressive therapy. Thus, IL-6 warrants further investigation as a putative therapeutic target in SAA. Highlights: Mass cytometry revealed CD4 + naïve T cells with hyperactivated JAK3/STAT3 pathway may be invloved in SAA pathogenesis. scRNA-seq uncovered CD4 + CAMK4 + naïve T cells were associated with aberrant immune activation in SAA development. Aberrant activation of the IL6/JAK3/STAT3 pathway were seen in Th17-polarized CD4 + CAMK4 + naïve T cells from pediatric SAA. High levels of baseline serum cytokine IL-6 predict delayed hematopoietic response to IST in SAA. Abstract : Th17-polarized naïve T cells with IL6/JAK3/STAT3 activation show putative clinical significance in SAA.